7 Good doctoring: 'core writings' as an antidote to medical overactivity?. (20th August 2018) - Hjorleifsson, Stefan; Heath, Iona; Getz, Linn
Abstract : Background: Rather than considering the state of medicine as a result of impersonal 'scientific progress', we must see ourselves as members of a reflective, responsible community in charge of continuously developing and re-thinking the field. And to counteract too much medicine, medical professionals need a fine blend of factual knowledge, critical reasoning skills, human sensitivity and courage. A daunting challenge for future doctors will be to navigate an ocean of possibilities in terms of monitoring, testing, diagnoses and interventions. We believe competent adherence to a 'less is more' strategy can safeguard genuine medical needs and protect patients from excessive burdens of treatment, in a socially accountable manner (overall cost containment). However, this will not materialise simply from epidemiological analysis of harm accruing from medical overactivity. Good doctoring springs out of a complex maturation process which involves the breakdown of medical silo-thinking in favour of a generalist perspective where doctors interact with patients as whole persons in a wider context, zoom in on medical essentials, and deal compassionately and wisely with the fundamental uncertainties of human existence. How can good, temperate doctoring be promoted? One answer might lie in stimulating, collective encounters with selected 'core writings' from the generalist medical literature. By core writings, we mean texts authored by professional role models who, from specific and recognizable perspectives, have identified viable principles of moderation and courage in solidarity with medicine's moral mandate. Aim: To explore the idea that well-tutored encounters with core generalist writings can help curb medical overactivity in an era of unprecedented belief in the powers of technology and overwhelming availability of medical (dis)information. Outcomes: Raised awareness and moral purpose among participants to resist overuse in their different capacities as practitioners, policymakers, researchers, educators, etc. Format: Brief plenary presentations focusing on how we currently use core generalist texts in Scandinavian general practice (family medicine) to nurture wisdom, moderation and courage. We will include examples from our own library that demonstrate what we believe characterises a core text and why we think it can have a significant, pedagogical impact. The main part of the workshop then involves discussions where participants share reflections, constructive critique and new ideas. Examples of core generalist texts to curb medical overactivity include the writings of McCormick, Marmot, Tudor Hart, Greenhalgh, Gøtzsche, Malterud, Welch, Kirkengen and Gawande. However, our menu is still in the making, and new ideas are welcome. Please join in!